Tinjauan Kritik Sastra Feminis dan Nilai Pendidikan Karakter dalam Novel Langit Mendhung Sajroning Pangangen Karya Tulus Setiyadi - Yuspitasari, Ajeng Virdianeta; Waluyo, Budi; Sulaksono, Djoko (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
The aims of this research was to identify feminism literary critism along with implementation character educational value in Langit Mendhung Sajroning Pangangen novel by Tulus Setiyadi . The research was a Langit Mendhung Sajroning Pangangen by Tulus Setiyadi javanese novel and interview. The sampling technique that used in this research was purposive sampling. The data was collected was used document analysis and interview. Techniques used for the data validity test were triangulation of theory and triangulation of data resources. Data analysis used interactive data model was includes: (1) data collection; (2) data reduction; (3) data display; and (4) conclusion drawing. The result of this research concluded as follows: (1) there are forms injustice againts women on the character Yani in Langit Mendhung Sajroning Pangangen novel by Tulus Setiyadi; and (2) there are character educational value includes: hard work, independent, social care, friendly/communicative, love the homeland, honest, and responsibility in Langit Mendhung Sajroning Pangangen novel by Tulus Setiyadi. The result of this research at least give some description andreference for student how to behave and maintain attitude againts woman and become a reference in implementing character building in daily life.